Voiceover Narration in Screen Works of Documentary and Television Journalism - Baryshnikov, K.B. (Телекинет)
The voiceover text promotes a correct and creatively adequate method of harmonizing the synchronous segment, the overall drama, and the development of the plot lines of the film’s characters and on-screen events and, as a result, organically accurate perception of the screen work as a whole by the audience in the context of the author’s idea and super-task. Today’s on-screen media often has a dismissive, formal attitude towards voiceover narration, creative ways, techniques and methods of its reproduction as an important segment of the literary and dramatic basis of a screen work, the commentary of screen events and the creation of an emotional and psychological atmosphere for the perception of a television program or film by the audience. In the context of this study, we offer less and more successful examples of working with voice-over author’s and narrator’s texts in the works of Russian screenwriters and directors of film and television journalism that have been little studied by documentary film historians, film critics and cultural scientists.